Development of Social Sciences in Dissertations of Immanuel Wallerstein - Implications for the Theory of International Relations - Rosicki, Remigiusz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The paper presents an analysis of the social science development concept of Immanuel Wallerstein. In general terms we can say that the development of social sciences was based on a process of emancipation of individual subjects of research and validation of research methods. I. Wallerstein drew attention to the process of emancipation of individual disciplines, therefore we can talk about the separation of philosophy, followed by social sciences and, negatively evaluated by I. Wallerstein, applied social sciences. With the constitution of individual disciplines we dealt with the process of polarising methodological positions, which can be roughly described as the concept of two cultures. The text describes the following issues: (1) the directions of emancipation of scientific disciplines, (2) the processes of emancipation of scientific disciplines, (3) the dynamics of changes in social sciences, (4) the effects of changes occurring in sciences. In addition to the main assumptions of I. Wallerstein on science, the text attempts to confront these assumptions with the achievements of T.S. Kuhn, R.K. Merton and C.W. Mills. The aim of the article is to point out the implications for the “theory of international relations” deriving from the general trends in the development of social sciences. This issue has come down to only selected issues of: microscopisation, idealisation, metaphorical use, deformation, transcendentalisation, fictionalisation and fetishisation of notions in the “theory of international relations”. The aim of the article is to point out the implications for the theory of international relations deriving from the general trends in the development of social sciences. This issue is presented by focussing on selected questions of: microscopisation, idealisation, methaporical use, deformation, fictionalisation and fetishisation of notions in the theory of international relations.

Artykuł przedstawia analizę koncepcji rozwoju nauk społecznych Immanuela Wallersteina. W ogólnym zarysie można powiedzieć, że rozwój nauk społecznych opierał się na procesie emancypacji poszczególnych przedmiotów badań i uprawomocnienia się metod badawczych. I. Wallerstein zwracał uwagę na proces emancypacyjny poszczególnych dyscyplin, dlatego też możemy mówić o wyodrębnieniu się filozofii, w dalszej kolejności nauk społecznych oraz negatywnie ocenianych przez I. Wallersteina nauk społecznych stosowanych. Wraz z konstytuowaniem się poszczególnych dyscyplin naukowych mieliśmy do czynienia z polaryzacją stanowisk metodologicznych, które to w skrócie można określić pojęciem dwóch kultur. W tekście podjęto następująca problematykę: (1) kierunki emancypacji dyscyplin naukowych, (2) procesy emancypacyjne dyscyplin naukowych, (3) dynamikę zmian w naukach społecznych, (4) skutki zmian występujących w naukach. Oprócz głównych założeń myśli I. Wallersteina na temat nauki w tekście podjęto próbę konfrontacji tych założeń z dorobkiem T. S. Kuhna, R. K. Mertona i C. W. Millsa. W artykule wskazano implikacje dla teorii stosunków międzynarodowych w związku z ogólnymi procesami rozwoju nauk społecznych. Problematyka ta została sprowadzona do wybranych kwestii: mikroskopizacji, idealizacji, metaforyki, deformacji, transcendentalizacji, fikcjonalizacji i fetyszyzacji pojęć w teorii stosunków międzynarodowych.
Rozwój nauk społecznych w rozważaniach Immanuela Wallersteina - implikacje dla teorii stosunków międzynarodowych
Keywords: Social sciences; Nauki społeczne; Theory of international relations; Teoria stosunków międzynarodowych; Immanuel Wallerstein; Immanuel Wallerstein